Variations within a subtype: Developmental surface dyslexias in English. (September 2018) - Kohnen, Saskia; Nickels, Lyndsey; Geigis, Leonie; Coltheart, Max; McArthur, Genevieve; Castles, Anne
Abstract: Surface dyslexia is characterised by poor reading of irregular words while nonword reading can be completely normal. Previous work has identified several theoretical possibilities for the underlying locus of impairment in surface dyslexia. In this study, we systematically investigated whether children with surface dyslexia showed different patterns of reading performance that could be traced back to different underlying levels of impairment. To do this, we tested 12 English readers, replicating previous work in Hebrew (Gvion & Friedmann, 2013; 2016; Friedmann & Lukov, 2008; Friedmann & Gvion, 2016). In our sample, we found that poor irregular word reading was associated with deficits at the level of the orthographic input lexicon and with impaired access to meaning and spoken word forms after processing written words in the orthographic input lexicon. There were also children whose surface dyslexia seemed to be caused by impairments of the phonological output lexicon. We suggest that further evidence is required to unequivocally support a fourth pattern where the link between orthography and meaning is intact while the link between orthography and spoken word forms is not functioning. All patterns found were consistent with dual route theory while possible patterns of results, which would be inconsistent with dual route theory, were not detected.